“The Physics Behind Everyday Motion: Understanding Newton's Laws” (International Journal of Food and Nutritional Sciences, 2022)
Newton's laws of motion form the foundation of classical mechanics, describing how objects move in response to forces. These principles are not only essential for understanding complex physical systems but also govern everyday experiences. This paper explores the three laws of motion proposed by Sir Isaac Newton, examining their implications and applications in daily life. Through practical examples and simple experiments, it will illustrate how these laws explain the movement of various objects, from vehicles on the road to the behavior of sports equipment. By understanding these laws, it gains insight into the fundamental principles governing motion and the world around us.